School Leadership in the Changing Context of School Education - Khandpur, Nimrat Kaur (Voices of Teachers and Teacher Educators, 2019)
The role of school leadership is critical in determining the effectiveness of schools and thereby of learning. This paper examines the changing discourse around school leadership, with focus on academic leadership and distributed leadership in the context of the school as a professional learning community. It then goes on to examine ideas around accountability, and then proposes a framework for capacity building to ensure leadership is operationalized at not only the school but also at the systemic level.